ANALISIS PERILAKU KESEHATAN REPRODUKSI ANAK-ANAK JALANAN DI ALUN-ALUN TAMAN MERDEKA KOTA PANGKALPINANG: Taufik Kurrohman (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
Street children generally do not have adequate knowledge about reproductive health and often have free sex. The results of interviews conducted with 5 male street children in the Taman Merdeka square in the city of Pangandaran admitted that they had used illegal drugs and had been rehabilitated, had had free sex such as kissing lips, hickey necks and others. This study aims to determine the analysis of the reproductive health behavior of street children in the Merdeka Square in the city of Pangandaran.The research method used is a qualitative research method which is presented in an exploratory descriptive manner through in-depth interviews, samples taken are 5 street children, and supporting informants 1 Pangkalpinang City Social Service official, 1 Pangkalpinang City SATPOL PP head and 5 street children's parents. The collection technique (purposive sampling) is the data collection technique using in-depth interviews and observation techniques, descriptive data analysis and presented in narrative form.The results show that the education level of street children is very low, street children do not know what reproductive health is, the environment of street children is very diverse, almost all of them live in any place, they also have free sex.The service that deals with the lives of street children should be able to provide socialization about good behavior so that street children can improve their bad habits into good ones.